High-quality laser-assisted biomass-based turbostratic graphene for high-performance supercapacitors. (February 2021) - Athanasiou, Michail; Samartzis, Nikolaos; Sygellou, Labrini; Dracopoulos, Vassileios; Ioannides, Theophilos; Yannopoulos, Spyros N.
Abstract: Preparing high-quality graphene-like structures and materials in a consistent and environmentally friendly way is still elusive. Recent advances have revealed that laser irradiation of proper precursors presents great potential and versatility towards realizing high-quality growth of graphene-like materials at low cost. Here, we present a detailed study of the laser-assisted transformation of homogenized dried Corinthian raisins (Vitis vinifera L., var. Apyrena) to graphene-like material. This is a one-step process, as the transformation of the raw biomass material takes place at ambient conditions. Diffraction, Raman scattering and electron microscopy have revealed that the structure of the laser-irradiated product is found to differentiate significantly from that of Bernal stacked graphitic carbon. This is the first demonstration of a laser-assisted growth of turbostratic phase via the decomposition of an organic compound. XPS analysis show a very high C/O ratio, i.e. 19, after the decomposition of a raw biomass material. The combination of turbostratic structure and almost complete oxygen species removal results in an ultralow sheet resistance of 10 Ω·sq −1, confirming the successful modification of the raw material to a graphene-like structure with high sp 2 hybridization degree. An additional merit of the current approach is that the process can induce both the growth of graphene-like structures on the irradiated target and in addition yields high-quality graphene-like powders. The latter have been used to prepare electrodes for symmetrical supercapacitors demonstrating superior performance compared to supercapacitors based on graphene prepared by other laser-assisted techniques. Graphical abstract: Image 1